Prospective and Longitudinal Study of Urogenital Dysfunction After Proctectomy for Rectal Cancer. Issue 9 (September 2016) - Adam, Jean-Philippe; Denost, Quentin; Capdepont, Maylis; van Geluwe, Bart; Rullier, Eric
Abstract : BACKGROUND: Urogenital dysfunctions after rectal cancer treatment are well recognized, although incidence and evolution over time are less well known. OBJECTIVE: We aimed to assess the evolution of urogenital functions over time after the treatment for rectal cancer. DESIGN: This is a prospective, longitudinal cohort study. SETTINGS: This study was conducted at a quaternary referral center for colorectal surgery. PATIENTS: A total of 250 consecutive patients treated for rectal cancer were prospectively enrolled for urogenital assessment. MAIN OUTCOME MEASURES: End points were the International Prostatic Symptom Score, the International Index of Erectile Function, and the Female Sexual Index obtained by questionnaires before (baseline status) and after preoperative radiotherapy and 3, 6, and 12 months after surgery. RESULTS: Overall, 169 patients (68%) responded to the questionnaires. The urinary function decreased temporary after irradiation in men (International Prostatic Symptom Score: 7.8 vs 4.9; p < 0.001). Sexual activity decreased significantly in women after radiotherapy ( p = 0.02), and in all patients after surgery ( p < 0.001). At 12 months, sexual activity in women declined from 59% before treatment to 36% ( p = 0.02). In men, sexual activity (82% vs 57%), erectile function (71% vs 24%), and ejaculatory function (78% vs 32%) decreased from baseline ( p < 0.001). Stage T3T4 tumors (OR = 5.72 (95% CI, 1.24–26.36)) and low rectal tumors (OR = 17.86 (95% CI, 1.58–20.00)) were independent factors of worse sexual function. LIMITATIONS: This study was limited by the proportion of uncompleted questionnaires, especially in women, and by its monocentric feature. CONCLUSIONS: Most patients experienced sexual dysfunction at 12 months after surgery for rectal cancer, and predictive factors for this dysfunction were related to characteristics of the tumor.